ANTIGEN OMP (OUTER MEMBRANE PROTEIN) salmonella typhi FAGA LOKAL YANG IMUNODOMINAN DAN SPESIFIK TERHADAP ANTIBODI PENDERITA DEMAM TIFOID - J. Nugraha; Rahayu Anggraini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Background of this research is that diagnostics of typhoid fever is still a health problem. Widal test, which is the mostly used test in Indonesia, frequently gives false positive results and is not reliable in endemic areas. On the other hand, the other confirmation test, bloodculture, is not sensitive and often give false negative results. OMP (Outer Membrane Protein) is known as a specific part of Salmonellatyphi and fragments of OMP still exist in the patient’s body since early infection until 2–3 weeks thereafter. In this study parts of OMPwhich react specifically with sera of typhoid fever in Indonesia were searched. These specific parts will then be developed as a diagnostickit for typhoid fever. Using Western Blot method, part of OMP will be searched, which is specifically react with sera of typhoid feverpatients in Indonesia. OMP derived from local phage type isolated in Indonesia was used. This OMP was separated with SDS-PAGE 12%and incubated with pooled sera of typhoid fever patients, and sera of control group, that is from Dengue haemorrhagic fever patientsand urinary tract infection with E. coli. Extraction of OMP was done by the method of Matsuyama. Contrary, this research failed to find a particular part of OMP which react specifically with sera of typhoid fever patients. There are certain parts of OMP which react also with sera of DHF & urinary tract infection patients. Our finding was different with the results from Malaysia, where it is reported thatantigen OMP 52 kD react specifically there. In order to develop a diagnostic tool for typhoid fever, we should consider another possiblespecific antigen other rather than using OMP.